2015
DOI: 10.1111/jgh.12879
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of short‐segment Barrett's esophagus using ultrathin transnasal endoscopy

Abstract: Background and Aim: Newly developed ultrathin transnasal endoscope, the GIF-XP290N, makes possible a resolving power similar to the GIF-H260 at a distance of 3 mm. We conducted surveillance of subjects with Barrett's esophagus using this ultrathin transnasal endoscopy. In Japan the lower margin of the lower esophageal palisade vessels is defined the gastroesophageal junction in deep inspiration. We diagnose Barrett's esophagus if columnar epithelium is present on the oral side of the gastroesophageal junction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
2
21
1
1
Order By: Relevance
“…In the present study, we made a diagnosis of BE when the length was ≥10 mm and noted a prevalence of 5.2% in subjects who underwent an endoscopic examination as part of an annual medical checkup. The prevalence of BE in our subjects was lower than that in other Japanese groups, including recent endoscopic studies that found that 20.8-85.9% of participants had BE, including ultra-short-segment BE ( 11 , 12 ). Therefore, a majority of endoscopically observed cases of SSBE in Japanese subjects seems to be <10 mm in length.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In the present study, we made a diagnosis of BE when the length was ≥10 mm and noted a prevalence of 5.2% in subjects who underwent an endoscopic examination as part of an annual medical checkup. The prevalence of BE in our subjects was lower than that in other Japanese groups, including recent endoscopic studies that found that 20.8-85.9% of participants had BE, including ultra-short-segment BE ( 11 , 12 ). Therefore, a majority of endoscopically observed cases of SSBE in Japanese subjects seems to be <10 mm in length.…”
Section: Discussioncontrasting
confidence: 78%
“…Indeed, the rate of incidence of adenocarcinoma development in the esophagogastric junction has also been gradually increasing in Asia ( 3 , 7 - 10 ). In Japan, while the prevalence of long-segment Barrett's esophagus (LSBE) is rare, the number of cases of adenocarcinoma developing from short-segment Barrett's esophagus (SSBE) has increased ( 3 , 7 - 12 ). As a result, patients with SSBE are considered to be the main population in Asian countries requiring endoscopic surveillance to detect esophageal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…13,22,68 Catanzaro et al 13 Table 1. 6,7,9,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][27][28][29][30][32][33][34]37,38,[40][41][42][43][44]46,49,50,52,53,[56][57][58][59][60]62,64,[68][69][70][71][72]…”
unclassified
“…Ultra-thin nasal endoscopes now exist and appear to be able to detect BE reasonably accurately. 53 54 The issues of scope reprocessing may also have been overcome with a disposable over-sheath. 55 Cytosponge A capsule-on-a-string cytology collection device developed in Cambridge (the Cytosponge), coupled with an immuno-based assay, has a high sensitivity for detecting BE without endoscopy.…”
Section: New Ways Of Monitoringmentioning
confidence: 99%